Methods of SOC Estimation of Li-Ion Batteries. (18th November 2019) - Cipin, Radoslav; Toman, Marek; Prochazka, Petr; Pazdera, Ivo
Abstract : This paper deals with problems with the estimation of the state of charge of Li-ion batteries. There are shown and discussed two basic methods for estimation of the state of charge. There are discussed essential problems with an estimation based on the so-called Coulomb counting method and based on an equivalent circuit of Li-ion battery.